Combination of Antiretroviral Drugs and Radioimmunotherapy Specifically Kills Infected Cells from HIV-Infected Individuals - Tsukrov, Dina; McFarren, Alicia; Morgenstern, Alfred; Bruchertseifer, Frank; Dolce, Eugene; Gorny, Miroslaw K.; Zolla-Pazner, Susan; Berman, Joan W.; Schoenbaum, Ellie; Zingman, Barry S.; Casadevall, Arturo; Dadachova, Ekaterina (Frontiers in Medicine, 2016)
Eliminating virally infected cells is an essential component of any HIV eradication strategy. Radioimmunotherapy (RIT), a clinically established method for killing cells using radiolabeled antibodies, was recently applied to target HIV-1 gp41 antigen expressed on the surface of infect-ed cells. Since gp41 expression by infected cells is likely down-regulated in patients on an-tiretroviral therapy (ART), we evaluated the ability of RIT to kill ART-treated infected cells us-ing both in vitro models and lymphocytes isolated from HIV-infected subjects. Human peripheral blood mononuclear cells (PBMCs) were infected with HIV and cultured in the presence of two clinically relevant ART combinations. Scatchard analysis of the 2556 human monoclonal anti-body to HIV gp41 binding to the infected and ART-treated cells demonstrated sufficient residual expression of gp41 on the cell surface to warrant subsequent RIT. This is the first time the quantification of gp41 post-ART is being reported. Cells were then treated with Bismuth-213-labeled 2556 antibody. conjugated to the human monoclonal antibody 2556, which binds to HIV gp41. Cell survival was quantified by Trypan blue and residual viremia by p24 ELISA. Cell surface gp41 expression was assessed by Scatchard analysis. The experiments were repeated using PBMCs isolated from blood specimens obtained from 15 HIV-infected individuals: ten on ART and five ART-naive. We found that 213Bi-2556 killed ART-treated infected PBMCs and reduced viral production to undetectable levels. ART and RIT co-treatment was more effective at reducing viral load in vitro than either therapy alone, indicating that gp41 expression under ART was sufficient to allow 213Bi-2556 to deliver cytocidal doses of radiation to infected cells. This study provides proof of concept that 213Bi-2556 may represent an innovative and effective targeting method for killing HIV-infected cells treated with ART, and supports continued development of 213Bi-2556 for co-administration with ART towards an HIV eradication strategy.